(untitled) (Research, Society and Development, 2021)
The jackfruit is consumed in natura or processed form, contributing to the generation of waste. Processing technologies, such as drying, are applied aiming at high quality products meeting market demands. Thus, the aim was to study the drying kinetics of jackfruit residues in an oven at 40, 50 and 60° C and in a microwave oven, and to adjust mathematical models to experimental data. The drying kinetics were determined by weighing the samples at regular intervals, until they reached equilibrium, and then the dry masses were determined. The Wang & Singh model represented oven drying at all temperatures studied, presenting the best values of coefficient of determination and the lowest mean square and chi-square deviations. Bark, central axis, mesocarp and seed dried at 60 ° C had a water content of 5.65, 4.94, 6.42 and 6.36% after 240, 300, 360, 300 min, respectively. The Page model represented the drying in a microwave oven and the heating ramp of the farinaceous was 3 cycles of 5 min at 100% power. Bark, central axis, mesocarp and seed had final water content of 9.57, 7.48, 7.47 and 6.24% after microwave drying. Therefore, the use of jackfruit residues becomes relevant, since they can be processed to generate new food products.